The Role of Vaccines in the Prevention of HPV Cervical Cancer in Iran between (2018 -2020) - Faegheh Miryousefiata; Sareh Sangy (Budapest International Research in Exact Sciences (BirEx) Journal, 2021)
ervical cancer is one of the leading causes of death in women of childbearing age in developing countries Are related. The HPV study is the fourth most malignant disease in women in the world. 15% of cervical cancers with the virus and cervical cancer was performed. The present HPV aims to investigate the role of vaccines in the prevention of infection. This study reviews information between 2018 and 2020 in Iran by searching databases. The most common sexually transmitted infection is self-limiting. HPV in men and women. HPV vaccination, which is associated with the development of oral-anal cancers, including cervical cancer and genital warts, HPV infection prevents. Vaccination Gardasil vaccine can provide up to 11% protection against cervical cancer The new nine are up to 19% effective against highly malignant cancers of the cervix and even the vagina. Increase day ads and ways of transmission and pathogenesis and treatment of vaccination of this virus leads to improved control of HPV over the prevalence Disease and ultimately controlling the consequences of the virus as well as the possibility of eradicating cervical cancer in decades The future will be.